Putting the S back in corporate social responsibility: A multilevel theory of social change in organizations - Aguilera, Ruth V.; Rupp, Deborah E.; Williams, Cynthia A.; Ganapathi, Jyoti (Academy of Management Review, 2007)
We provide a multilevel theoretical model to understand why business organizations are increasingly engaging in corporate social responsibility (CSR) initiatives and thereby exhibiting the potential to exert positive social change. Our model integrates theories of organizational justice, corporate governance, and varieties of capitalism to argue that organizations are pressured to engage in CSR by many different actors, each driven by instrumental, relational, and moral motives. We conclude by highlighting empirical questions for future research and discussing some managerial implications.